This INCREASING STUDENTS VOCABULARY THROUGH INDEPENDENT READING TO THE SEVENTH GRADE STUDENTS OF SMP N 3 LANGSA - irma dewi isda (Journal of Education, Linguistics, Literature and Language Teaching, 2018)
This research has purpose to prove teaching vocabulary through independent reading increase students’ interest in studying vocabulary, to know the advantages of learning vocabulary through independent reading and to find out and solved the problems that faced by the students in teaching vocabulary through independent reading. The populations of this research are the whole students of SMP Negeri 3 Langsa and as the samples of this study is one class of the seventh grade students of SMP Negeri 3 Langsa, which consist of 39 students. To get the relevant data, the researcher used library research and field research. The data in this study has analyzed by using Mean formula suggested by Anas Sudijono. From the calculation of the data showed that, the result of mean from pretest is 61 and mean from post test is 69, from the result it happened improvement about 8 point. From the result the researcher conclude teaching vocabulary through independent reading increase students’ achievement in studying vocabulary.